Mahabbah Kepada Allah SWT dan Para Makhluk-Nya - Suharyanto, Ernaka Heri Putra; Akbar, Aziz (Adabuna : Jurnal Pemikiran dan Pendidikan, 2022)
At first glance, the meaning that appears in the minds of some people when reading or hearing the word mahabbah is about wird or reading that causes the potential reader to be loved by the desired target. There is also the meaning of the word mahabbah as a feeling of affection so that it results in ignoring his own interests because he prioritizes the interests of those he loves even at sacrifice. The method used in writing this article is in the form of literature review or based on literature review by reading, understanding and analyzing the necessary reference sources in accordance with mahabbah studies in everyday life.